PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN DAN CITRA MEREK TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN SEBAGAI VARIAEL INTERVENING - Ulfa Syahria Balgis; N. Rachma; M. Hufron (E-JRM : Elektronik Jurnal Riset Manajemen)
ABSTRACT This study aims to examine and analyze the direct and indirect effects of product quality, service quality and brand image on customer loyalty through customer satisfaction Matahari Departemen Store Malang Town Square.The population of this study are the consumers of Matahari Department Store Malang Town Square and the sample of this study was 94 respondents. Data collection uses questionnaires with accidental sampling technique. Analysis of this research data using SPSS version 16 help. Data testing techniques used in this study include validity test, reliability test, normality test, path analysis, and testing the research hypothesis. The results of the analysis show that product quality, service quality and brand image have a direct effect on satisfaction, product quality, service quality and brand image directly influence customer loyalty, satisfaction has a direct effect on customer loyalty and product quality, service quality and brand image indirect effect. towards customer loyalty through satisfaction as an intervening variable Keywords: Product quality, Service quality, Brand image, Satisfaction, Loyalty